Experimental research on the spontaneous combustion of coal with different metamorphic degrees induced by pyrite and its oxidation products. (15th June 2022) - Ding, Cong; Li, Zongxiang; Wang, Jiren; Duanmu, Pengbo; Lu, Bing; Gao, Dameng
Highlights: Pyrite oxidation products have a great positive effect on coal self-heating. Fe 2+ has a stronger ability to promote the natural oxidation of low-rank coal. Fe 3+ and Fe 2+ promote the oxidation of hydroxyl and aliphatic hydrocarbons. Abstract: To study the effect of pyrite on the spontaneous combustion of coal, three types of low-sulfur coal samples with different metamorphic degrees, namely HQL (lignite), DR (bituminous), and YQ (anthracite), were selected to impregnate FeS2 and its oxidation products. The results of thermal analysis experiments showed that Fe 3+, Fe 2+, and H + had evident catalytic effects on the low-temperature oxidation of the three samples, with the catalytic order being Fe 3+ > Fe 2+ > H + . A self-heating experiment on coal showed that Fe 3+ reduced the shortest ignition time of the above samples by 55.4%, 49.8%, and 45.3%, respectively, and its catalytic ability was the strongest. With the increase in the degree of metamorphism, the promotion effect of Fe 2+ gradually decreased, and the promotion effect of H + on the low-temperature oxidation of DR was the greatest. Through an FTIR analysis, it was found that Fe 3+, which is a strong oxidant and free radical, could catalyze the oxidation reaction of the active structures –CH2 - and –OH. Fe 2+ promoted O2 and H + in low-rank coals to generate H2 O2 and made them to further generate hydroxyl radicals to oxidize the structure in the coal. In high-rank coals, Fe 2+ catalyzed the oxidation reaction in the coal mainly through its oxidizability with decreasing H + concentration. H + promoted the low-temperature oxidation of coal mainly by adsorbing oxygen and removing ash to increase the specific surface area. Combining the oxidation reaction of pyrite under dry and wet conditions, pyrite could catalyze the spontaneous combustion of low-rank coals under dry conditions. Under humid conditions, pyrite could better catalyze the spontaneous combustion of high-rank coals.